Social media overload and proactive–reactive innovation behaviour: A TTSC framework perspective - Gao, Suying; Zhao, Xue (International journal of information management, 2024)
Based on the transactional theory of stress and coping, a theoretical model of social media overload and employees’ proactive–reactive innovation behaviour is constructed, in which emotional exhaustion and knowledge hiding serve as mediating variables, and the intrinsic mechanism of action among the variables is explained based on the conservation of resources theory. Study 1 tested the research model using data from 376 internal corporate social media users and their leaders. The results show that emotional exhaustion and knowledge hiding play a chain-mediating role between social media overload (information, communication, and social overload) and employees’ proactive and reactive innovation behaviours. Study 2 repeated Study 1′s hypothesis test using data from 406 internal corporate social media users. Most conclusions are consistent with Study 1, except that the relationships between communication overload and emotional exhaustion and between knowledge hiding and proactive innovation behaviour are not supported. These inconsistent conclusions may be attributed to the COVID-19 pandemic. Study 2 revealed the moderating role of digital fluency. This study enriches the research on the dark side of social media use, expands the research perspective on social media overload, and provides new support for employees’ proactive–reactive innovation behaviours. •Reveals the relationship between social media and innovation behaviour.•Explores the dark side of social media use in the workplace using the TTSC model.•Advances a proactive-reactive perspective on innovation behaviour in social media.•Validates the impact of digital fluency on the efficiency of social media use.•Improve employees’ social media usage, digital fluency, and innovation behaviours.